Bridging Faith and Fluency: An Identity-Responsive Instructional Model for Islamic-Based English Speaking Materials - Harir Mubarok; Basori Basori; Nur Fitria Anggrisia; Agwin Degaf (FKIP Universitas Lampung, 2026)
This study aims to develop and evaluate an Islamic-based English speaking textbook as an identity-responsive instructional model, defined as a pedagogical approach that integrates learners’ cultural and spiritual identities into CEFR-oriented communicative speaking tasks. This research employed an educational research and development design using the ADDIE model. The textbook was designed, validated, and implemented through pre- and post-tests of CEFR A2–B1 speaking tasks, student questionnaires, classroom observations, and after-class interviews involving 58 students and lecturers at SKM Islamic University. Spiritual identity engagement was examined through thematic analysis supported by indicators of importance, ease, and involvement demonstrated during speaking activities. Expert validation was conducted to evaluate linguistic accuracy, cultural relevance, and content quality. Statistical results show notable improvements in students’ speaking performance, with fluency increasing from 2.8 to 4.1, vocabulary from 2.7 to 4.0, pronunciation from 3.1 to 4.2, and grammar from 2.9 to 3.8. Thematic analysis indicates that integrating Islamic values into communicative tasks fosters meaningful participation, confidence, and strengthened expression of spiritual identity. Experts confirmed the textbook’s linguistic soundness and cultural alignment. The findings demonstrate that instructional materials incorporating cultural and spiritual identity elements can effectively support students’ communicative ability and value engagement. The developed textbook shows strong pedagogical potential and competitive advantages over comparable materials used in Islamic educational settings. Keywords: english, instructional materials, islamic values, language learning, speaking skills.